Pemberdayaan Rakyat dalam Reformasi Pendidikan - -, Sutoyo (Joglo, 2006)
ABSTRACTEmpowering people in educational reformation is an essensial problem because in fact the educational problem is an endless-issue to discuss. it means that the problem needs more solutions. The reformation should be realized by employing educational democrazy, including institutional structure, educational system, personnel, and curriculum.To Reform in educational field really needs the solutions and development, including increasing the quality of human resources, the quality and quantity of educational facilities, improving and completing the curriculum, and increasing the quality of education process. Key word : People empowering, Educational reform.